Role of oxygen in enhanced fatigue cracking in a PM Ni-based superalloy: Stress assisted grain boundary oxidation or dynamic embrittlment?. (15th July 2018) - Jiang, R.; Proprentner, D.; Callisti, M.; Shollock, B.; Hu, X.T.; Song, Y.D.; Reed, P.A.S.
Highlights: Oxides forming under cyclic and static load consist of similar layered structures. Microscopically grain boundary oxidation is closely related to strain localisation. SAGBO makes a dominant contribution to fatigue crack initiation and early propagation. Grain boundary oxidation at the fatigue crack tip is ΔK- and da/dN-dependent. FCP is a result of competing effects of oxygen-related damage and mechanical damage. Abstract: The role of oxygen in enhanced fatigue cracking in an advanced Ni-based superalloy for turbine disc application has been evaluated in fatigue crack initiation and propagation stages along with static oxidation tests. It is found that the grain boundary oxide intrusion has a layered structure. The microstructure- and deformation-dependent grain boundary oxidation dominates the fatigue crack initiation and early propagation processes. As the crack propagates, this contribution arising from oxidation damage may gradually be overtaken by dynamic embrittlement processes until the mechanical damage outstrips the oxygen-related damage, resulting in a transition from intergranular to transgranular crack propagation.